The Theory of Absolute Governance Between Machiavelli and Hobbes - Yunis Kakamam Mirza (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research: (The theory of absolute governance between Machiavelli and Hobbes(. It consists of an introduction, two sections and a conclusion. The first section is devoted to the analysis (theory of absolute governance) from the point of view of Machiavelli's political philosophy. Machiavelli's life and development are described. Also: ("Human Nature, Morality, and Politics. Types of governance, Virtue and Fortuna's Concepts, President's Characteristics"), Analyzed. For this reason, benefit is taken from Machiavelli's masterpiece, entitled The Prince. Also, the second part of the study is devoted to discussing the political philosophy of Thomas Hobbes about the theory of governance. Of course, Hobbes's views, in this regard, are still valuable. In this section, in the two main chapters, which we later divide into several different parts, we have tried to analyze the political philosophy of Thomas Hobbes. Such as: ("Human nature and its characteristics. The state, types of state, Natural laws and social covenants, Rights and duties of leader and people." Finally, in addition to highlighting the results, we have tried to compare Machiavelli's and Hobbes' views.